2019
DOI: 10.1002/tesj.438
|View full text |Cite
|
Sign up to set email alerts
|

Comparing language skill priorities among TESOL faculty and ESL students bound for English‐medium universities

Abstract: With growing evidence that learners of English as a second language (ESL) may face linguistic disadvantages when studying at English-medium universities, it is appropriate to identify the most effective ways to optimize their preparation. One area of interest is the relative importance university professors across disciplines place on language skills in their classrooms and how this might inform ESL teaching and learning. Thus, this study sought to identify perceptions of TESOL faculty and their ESL learners i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 45 publications
(53 reference statements)
1
10
0
Order By: Relevance
“…These scholars observed that to these content professors, listening and reading were the most important language skills for students beginning their academic careers. Other research has found similar results, suggesting that TESOL practitioners viewed listening and reading as the most important skills their students needed to master (Hartshorn et al, 2019).…”
Section: The Importance Of Listening Instructionsupporting
confidence: 57%
See 2 more Smart Citations
“…These scholars observed that to these content professors, listening and reading were the most important language skills for students beginning their academic careers. Other research has found similar results, suggesting that TESOL practitioners viewed listening and reading as the most important skills their students needed to master (Hartshorn et al, 2019).…”
Section: The Importance Of Listening Instructionsupporting
confidence: 57%
“…Most scholars agree that listening is vitally important for second language learners (e.g., Kurita, 2012;Nunan, 2002;Renukadevi, 2014). Nevertheless, listening is often neglected compared to other language skills (Vandergrift & Goh, 2012) and practitioners tend to feel least prepared to teach listening compared to other skills despite the fact that listening is often perceived as most important in academic settings (Hartshorn et al, 2019). We find it unacceptable that most practitioners feel the least prepared to effectively teach one of the most important language skills.…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…It has also become the information content delivery in tertiary education worldwide (Richards & Pun, 2021). Historically, teaching and learning English as a second or foreign language has been emphasized as the worldwide domain of teaching language skills (Yaccob et al, 2022b;James Hartshorn et al, 2019). In Malaysia, universities have long used English as the language of communication as it has been learned as a Second Language (L2) since school (Yaccob et al, 2022a).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, with growing evidence that learners of English may face linguistic disadvantages when studying at English‐medium universities, it seems necessary to identify the most effective ways to optimize students' preparation. A study conducted by Hartshorn et al (2019) found that TESOL faculty and content professors both considered reading and listening as the most important language skills for university‐level students to possess. Although many postsecondary students acquiring English for academic purposes have strategies for writing an essay or giving an oral presentation, very few have strategies for how to listen .…”
Section: Introductionmentioning
confidence: 99%